Impact of Organisational Culture on Organisational Commitment: Evidence from Pakistan - Bilal Nawaz Kayani (Journal of Accounting, Business and Management (JABM), 2023)
This research paper investigates the impact of organisational culture on organisational commitment of employees working in hotel industry of Pakistan. As organisational culture plays a pivotal role in the growth and success of any organisation. This study examines organisational culture’s influence on organisational commitment on a sample of two hundred and thirty-seven employees with more than ten years of working experience in hotel industry in Pakistan. SPSS is used for data analysis and mean; standard deviation is analysed as a part of descriptive statistics. To test research hypothesis Pearson correlation and regression analyses are used. Questionnaires from the prior research study was adopted to measure research variables. Research findings are expected to fill up the gap in prior literature available by providing evidence on the impact of organisational culture on organisational commitment among employees of hotel industry in a developing country like Pakistan, as there is a lack of literature available on the research variables of organisational culture and organisational commitment within the context of the hotel industry. The research findings of this study reveals that all the organisational cultural dimensions have a significant positive influence on the organisational commitment of hotel industry employees.